The effect of Dimethoate on oxidative stress and antioxidant responses of Pontastacus leptodactylus - Aydin, Ayse Nur; Bulut, Hilal; Serdar, Osman (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Dimethoate (DMT) pesticide is one of the chemicals used to protect some agricultural areas from harmful organisms. DMT residues released directly or indirectly to the environment cause serious problems in nature. DMT residues mixed with the aquatic environment adversely affect aquatic organisms and this effect is carried to humans through the food chain. In this study, oxidative stress responses induced by DMT pesticide in Pontastacus leptodactylus were investigated. For this purpose, oxidative stress and antioxidant parameters Thiobarbituric acid reactive substances (TBARS), Glutathione (GSH), Superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX) caused by dimethoate (DMT) pesticide in P. leptodactylus at 17.5, 35, and 70 mgL-1 concentrations at 24 and 96 hours were investigated. Results were determined using ELISA kits. No significant difference was observed in GSH levels and SOD activities compared to control. Statistically significant differences were observed between decreases in CAT and GPx activities and increases in TBARS levels. SPSS 24.0 package program one-way ANOVA (Duncan 0.05) was used in the evaluation of biochemical analyzes. As a result, it was determined that DMT caused oxidative stress formation in P. leptodactylus and caused changes in enzyme activities.
El efecto del dimetoato sobre el estrés oxidativo y las respuestas antioxidantes de Pontastacus leptodactylus
Keywords: Dimethoate; Pontastacus leptodactylus; oxidative stress; antioxidant; biomarkers